Preventing Mild Steel Corrosion in 1.0 M HCl with Waterer Egyptian Wormwood Leaves and Stems (WEWLS) (Analyzing Thermodynamic and Adsorption Parameters) - Mohammed Al-Kilani Al Madani; Salah Abdullah Gnefid (African Journal of Advanced Pure and Applied Sciences, 2024)
Mild steels are particularly prone to corrosion in acidic environments, such HCl, which causes industries to suffer significant financial losses that are estimated to be in the billions of dollars each year. One tactic to reduce corrosion is to use corrosion inhibitors. Research has indicated that organic molecules—particularly those containing N, S, and O—have exhibited noteworthy inhibitory efficacy when it comes to the majority of synthetic organic corrosion inhibitor compounds. Unfortunately, most of these compounds are not only expensive but also toxic to living things. The main goal of this experiment was to determine the effects of adding different weights of Waterer Egyptian Wormwood Leaves and Stems (WEWLS) extract to a one mole aqueous HCl solution on mild steel material corrosion. The corrosion rate (CR), inhibitor efficiency (IE%), adsorption constants ( ), adsorption energies ( ), and adsorption isotherm models (Langmuir, Temkin, and Adejo Ekwenchi) were all taken into account in the weight loss technique. The weight loss experiment’s results showed that when inhibitor concentration increases, corrosion inhibition increases gradually. At an inhibitor concentration of (300 ppm), the maximum inhibition efficiency of (93.07%) was achieved. The effective adsorption of the inhibitor on the metal surface is confirmed by the adsorption measurements.